Political ecologies of water in South Africa: A literature review - (:unkn) unknown (My University, 2019)
Given the existence of a thriving epistemic community on water sciences, the high politicization of environmental issues in the country as well as the active mobilization of a grassroot movement inspired by environmental justice, South Africa appears to be an ideal case to study the development of a political ecology (PE) approach. Moreover, since the apartheid regime, water issues have long represented a marker of extreme inequality.This paper aims at drawing a panorama of the PE of water in South Africa, its main topics and approaches. In our definition, the PE of water is concerned with human–environment relations, with explicit considerations for power relations. In the first section, we identified texts that, according to this definition, constitute the core of the PE of water in South Africa, going beyond a mere “politics of water.” In the second section and in the discussion, we undertook an in‐depth analysis of the main topics addressed by authors, such as environmental flows, “free basic water policy,” prepaid water meters. PE of water is strongly connected to international debates about the link between water and power, but also capable of addressing in a critical way the specificities of the South African waterscape. It stems from this review that critical PE in urban settings in particular dominates the discipline. We could also note that the PE of water in rural areas tends to put a bigger emphasis on the “politics of ecology” whereas urban PE tends to focus more on the “ecology in politics,” although both thrive to examine the human–environment relations in an integrated manner. This article is categorized under: Human Water > Water Governance Human Water > Value of Water Human Water > Rights to Water
Keywords: African Research